2020
DOI: 10.31234/osf.io/6h52d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using language in social media posts to study the network dynamics of depression longitudinally

Abstract: Background: Network theory of mental illness posits that causal interactions between symptoms give rise to mental health disorders. This is thought to occur because positive feedback loops between symptoms trigger cascades of further symptom activation. Increasing evidence suggests that depression network connectivity is therefore a risk factor for transitioning and sustaining a depressive state. However, much of the evidence comes from cross-sectional studies that estimate networks across groups, rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…This necessitates taking a ‘trait’ perspective on the mental health symptoms we assessed and it is likely that our model is diluted by variations in state/episodic features of depression. However, in a recent study, we found that individuals’ use of depression-relevant text features in fact didn’t change significantly across within-subject periods of mental health and wellness, suggesting this may not be a major issue 63 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This necessitates taking a ‘trait’ perspective on the mental health symptoms we assessed and it is likely that our model is diluted by variations in state/episodic features of depression. However, in a recent study, we found that individuals’ use of depression-relevant text features in fact didn’t change significantly across within-subject periods of mental health and wellness, suggesting this may not be a major issue 63 .…”
Section: Discussionmentioning
confidence: 66%
“…Twitter data, by itself, has already proven an interesting testbed for nascent theories of mental health such as network theory, which for example, has struggled to acquire large enough longitudinal datasets to test some of its core predictions 62 . We recently found for example that using social media posts as a proxy for experience sampling allowed us to study a large cohort of individuals through a transition to a depressed state, detecting subtle network signatures of depression vulnerability 63 .…”
Section: Discussionmentioning
confidence: 99%
“…This necessitates taking a 'trait' perspective on the mental health symptoms we assessed and it is likely that our model is diluted by variations in state/episodic features of depression. However, in a recent study we found that individuals' use of depression-relevant text features in fact didn't change significantly across within-subject periods of mental health and wellness, suggesting this may not be a major issue [72].…”
Section: Limitationsmentioning
confidence: 72%
“…Twitter data, by itself, has already proven an interesting testbed for nascent theories of mental health such as network theory, which for example, has struggled to acquire large enough longitudinal datasets to test some of its core predictions [71]. We recently found for example that using social media posts as a proxy for experience sampling allowed us to study a large cohort of individuals through a transition to a depressed state, detecting subtle network signatures of depression vulnerability [72].…”
Section: Practical Utilitymentioning
confidence: 99%
“…To the best of our knowledge, this is one of the rst prospective longitudinal studies to use natural language collection 50 and the rst focused on maternal depression symptom prediction. Incorporating language inputs enables moderate predictive ability of depressive symptoms among peripartum patients in a large academic health system.…”
Section: Discussionmentioning
confidence: 99%